Evaluasi Lama Fermentasi Ampas Sari Kedelai dengan Aspergillus Ficuum Terhadap Kandungan Bahan Kering, Protein Kasar dan Serat Kasar - Rica Mega Sari; Alfian Asri; Yulika Rahma (Jurnal Peternakan Mahaputra, 2022)
This study aims to determine the effect of the length of fermentation time of soybean juice with Aspergillus ficuum on the dry matter, crude protein, and crude fiber content. Completely Randomized Design with 4 treatments and 5 replications for each treatment, used in this research. The treatments consisted of P0 fermentation for 0 days, P1 fermentation for 7 days, P2 fermentation for 9 days, and P3 fermentation for 11 days. The parameters measured were dry matter content, crude protein content, and crude fiber content. The results of the analysis of diversity showed that the length of fermentation of soybean juice with Aspergillus ficuum had a very significant effect (P<0.01) on dry matter content, crude protein content, and crude fiber content. From the results of the study, it can be concluded that the fermentation time of soybean juice with Aspergillus ficuum for 11 days gave optimum results seen from the dry matter content of 95.95%, crude protein content of 35.27% and crude fiber content of 10.99%.